The Impact of a Psychological Program on the Development of Physical Abilities of Combat Sports Practitioners at the National Sports High School: The Case of Male Athletes, Class of 2019/2020 - Lakrout , Samir (sports creativity, 2025)
The objective of our study is to demonstrate the effect of a psychological program on the development of physical abilities through a comparative analysis of results, highlighting the impact of the psychological aspect on performance improvement. The study includes 16 combat sports athletes from the National Sports High School who followed the same training program, except that half of these athletes did not receive psychological support. The other eight athletes, however, had a psychological program tailored to their individual profiles and training conditions. Next, various tests were administered using the Myotest device. The comparative analysis of the athletes' results reveals a significant difference in the average scores of the assessed physical qualities. Our study confirms that the presence of a psychological program is a crucial method for ensuring the development of an athlete's performance level.